Security unbound : enacting democratic limits - Huysmans, Jef. (Abingdon, Oxon : Routledge, 2014)
'Security concerns have mushroomed. Increasingly numerous areas of life are governed by security policies and technologies. Security Unbound argues that when insecurities pervade how we relate to our neighbours, how we perceive international politics, how governments formulate policies, at stake is not our security but our democracy. Security is not in the first instance a right or value but a practice that challenges democratic institutions and actions. We are familiar with emergency policies in the name of national security challenging parliamentary processes, the space for political dissent, and fundamental rights. Yet, security practice and technology pervade society heavily in very mundane ways without raising national security crises, in particular through surveillance technology and the management of risks and uncertainties in many areas of life. These more diffuse security practices create societies in which suspicion becomes a default way of relating and governing relations, ranging from neighbourhood relations over financial transactions to cross border mobility. Security Unbound demonstrates that governing through suspicion poses serious challenges to democratic practice. Some of these challenges are familiar, such as the erosion of the right to privacy; others are less so, such as the post-human challenge to citizenship.Security unbound provokes us to see that the democratic political stake today is not our security but preventing insecurity from becoming the organising principle of political and social life'--
1. Security unbound and democracy -- 2. Political reading of security -- 3. Insecurity as exception -- 4. Diffusing insecurities -- 5. Assembling suspicion -- 6. Surveillance, democracy, privacy -- 7. Security technology and democratic limits -- 8. Insecurity, democracy, political.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Privacy, Right of; Democracy; Electronic surveillance -- Social aspects; Electronic surveillance -- Political aspects; Information technology -- Social aspects; Information technology -- Political aspects; Social psychology; Social control